2021
DOI: 10.2147/dmso.s295451
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome and Factors Associated With It Among Adults of West Gojjam: A Community-Based Cross-Sectional Study

Abstract: Background Metabolic syndrome is a cluster of risk factors for cardiovascular diseases, indicating great clinical attention. However, much less attention has been given to metabolic syndrome in the study area. Objective The objective of this study is to determine the prevalence of metabolic syndrome and its associated factors in the adult population of West Gojjam zone, Ethiopia. Methods A community-based cross-sectional study was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…On the other hand, the study observed a 13.7% (95% CI: 7.04%- 20.40%) and 14.7% (95% CI: 7.83% - 21.58%) prevalence of MS among the control groups using NCEP ATP- III and IDF criteria, respectively. This finding is consistent with the study conducted in West Gojjam (17.3%) [ 14 ], in Mizan-Aman town (9.6%) [ 29 ], according to the modified NCEP-ATP III criteria, and in Eastern Ethiopia (20.1%) [ 30 ] and Nigeria (18%) [ 31 ] according to IDF criteria. However, it is low as compared with the pooled review among the Ethiopian population (27.92%) [ 13 ], a study from Ghana (35.9%) [ 32 ], and India (33.5%) [ 33 ] using IDF criteria.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the study observed a 13.7% (95% CI: 7.04%- 20.40%) and 14.7% (95% CI: 7.83% - 21.58%) prevalence of MS among the control groups using NCEP ATP- III and IDF criteria, respectively. This finding is consistent with the study conducted in West Gojjam (17.3%) [ 14 ], in Mizan-Aman town (9.6%) [ 29 ], according to the modified NCEP-ATP III criteria, and in Eastern Ethiopia (20.1%) [ 30 ] and Nigeria (18%) [ 31 ] according to IDF criteria. However, it is low as compared with the pooled review among the Ethiopian population (27.92%) [ 13 ], a study from Ghana (35.9%) [ 32 ], and India (33.5%) [ 33 ] using IDF criteria.…”
Section: Discussionsupporting
confidence: 91%
“…The sample size was determined using Epi Info version 7, by taking 27.4% as the prevalence of raised blood pressure, a common component of MS, among controls from a previous study [ 14 ] and 50.0% as the expected prevalence among epileptic patients, since there was no previous study in Ethiopia. By taking the 1:1 case-to-control ratio, 95% CI, and 86% power, the total sample size becomes 186.…”
Section: Methodsmentioning
confidence: 99%
“…However, the diversity of different positions did not allow us to extend to a specific group. Most studies in the literature have been conducted mainly on the general population [13,14] or on target groups, i.e. diabetics [2,15], hypertensives, and the obese [16,17].…”
Section: Discussionmentioning
confidence: 99%